Abnormal Splanchnic Regional Saturations in a Preterm Infant That Developed Necrotizing Enterocolitis Following a Red Blood Cell Transfusion. (October 2020) - Baserga, Mariana; Reich, Brixen; Braski, Katherine
Abstract : Background: Necrotizing enterocolitis (NEC) has been associated with red blood cell (RBC) transfusions in preterm infants. Near-infrared spectroscopy (NIRS) can be used to noninvasively monitor regional oxygen saturations (rSO2 ). Clinical Findings: This former 28-week female premature infant, 29 days old, received an RBC transfusion due to increased apneic spells and a hematocrit of 27%. Within 24 hours she developed abdominal distension and passed a bloody stool (Bell's stage 2 NEC on abdominal x-ray). She completed 7 days of antibiotics and nothing-by-mouth status and was discharged home on room air and oral feedings on day of life 70. Primary Diagnosis: We describe the presentation of NEC following a RBC transfusion in a preterm infant monitored with cerebral and splanchnic NIRS. Interventions: Mean rSO2 (cerebral and splanchnic) measurements were continuously recorded and calculated in 30-minute periods at baseline (prior to packed RBC transfusion), every hour during the RBC transfusion, and every 3 hours for the following 48 hours. Outcomes: In this infant, average baseline splanchnic rSO2 was low at 46.5%, and increased during transfusion to 65%. However, following the RBC transfusion and an enteral feeding, splanchnic rSO2 dramatically decreased to 26%, and remained low until the time of NEC diagnosis. Practice Recommendations: To develop awareness of the increased risk for NEC in premature infants with significant anemia that receive packed RBC transfusions. With further studies and education, NIRS could be a valuable tool for the nurses and medical team to identify these at-risk neonates.